A phase II, multi-center, open-label study to evaluate the safety and efficacy of YH003 in combination with toripalimab (anti-PD-1 mAb) in patients with unresectable/metastatic pancreatic ductal adenocarcinoma (PDAC) - Shen, Lin; Ananda, Sumitra; Cao, Dan; Han, Catherine HyeWon; Coward, Jermaine; Chao, Yee; Li, Wei; Hari Dass, Prashanth; Hsu, Chih-Hung; Nagrial, Adnan; Huang, Yuan; Ganju, Vinod; et al. (Journal of clinical oncology, 2024)
4146Background: Pancreatic cancer therapy remains a formidable challenge. Although chemotherapy offers tumor control and clinical stabilization, both standard regimens are limited in response durability and incur toxicity. YH003, a humanized agonistic anti-CD40 monoclonal antibody specifically recognizes and agonizes CD40 to enhance immune responses, has demonstrated good safety and promising antitumor activity in Phase I clinical studies in patients with solid tumors. Here, we report the results of the phase II study of YH003 plus Toripalimab with/without chemotherapy, as 1L or 2L treatment in patients with metastatic PDAC. Methods: Patients with unresectable/metastatic (u/m) PDAC were enrolled into two Cohorts. In the second and plus line (2L+) Cohort, patients who had confirmed progressive disease during treatment with first line standard of therapy were enrolled and received 0.3 mg/kg YH003 plus 240 mg Toripalimab, iv, every 21 days. In the 1L Cohort, patients without any prior systemic treatment were enrolled and received 0.3 mg/kg YH003 plus 240 mg Toripalimab plus nab-paclitaxel + gemcitabine, iv, every 21 days. The treatment continued for 12 months if subject was deriving an ongoing clinic benefit. The primary endpoint was overall Response Rate (ORR) by investigator's assessment per RECIST 1.1. The medium Progression-Free Survival (mPFS) and Overall Survival (mOS) were secondary endpoints. Results: A total of 92 patients were enrolled including 45 subjects for the 2L+ Cohort and 47 subjects for the 1L Cohort. In the 2L+ Cohort, 40 (including 14 Caucasians) of 45 patients had at least 1 evaluable post-treatment tumor assessment, the unconfirmed ORR was observed in 4 patients (10.0%) with 4 partial responses (PR). 10 patients (25.0%) had stable disease (SD), and the Disease Control Rate (DCR) was 35.0%. The mOS was 7.23 months. For the Caucasian subgroup (n = 14), the ORR was 7.1%, DCR was 50%, mPFS was 2.25 months and mOS 9.54 months. For the 1L Cohort, 43 (including 10 Caucasians) of 47 patients had at least 1 evaluable post-treatment tumor assessment, the unconfirmed ORR was observed in 12 patients (27.9%) with 1 CR and 11 PR. 23 patients (53.5%) had SD, and the DCR was 81.4%. The mOS time was 12.12 months. For the Caucasian subgroup (n = 10), the ORR was 50%, DCR was 100%, mPFS was 11.27 months and mOS 19.78 months. The grade 3 or above adverse events that occurred in the 92 patients were 57.8% (26/45) in 2L+ Cohort and 74.5% (35/47) in 1L Cohort. There is no significant safety signal from the study. Conclusions: The results of the phase II study have shown that YH003 plus Toripalimab with/without chemotherapy, as 1L or 2L treatment in patients with u/m PDAC have promising antitumor activity and response durability, especially in the Caucasian subgroups. Both treatment regimens are well tolerated. Clinical trial information: NCT05031494.